An overview of insights and updates on TTN mutations in cardiomyopathies - Saha, Sarmistha; Temaj, Gazmend; Telkoparan-Akillilar, Pelin; Chichiarelli, Silvia; Saso, Luciano (Frontiers in Pharmacology, 2025)
Within the heart muscle, the largest sarcomeric protein is titin (TTN). The heart expresses two principal isoforms, N2B and N2BA, which arise from alternative splicing of the TTN gene. These isoforms span four distinct regions of the sarcomere: the Z-line, I-band, A-band, and M-line. Titin, encoded by the extensive TTN gene consisting of 364 exons, plays a critical role in the structural integrity, development, mechanical properties, and regulation of both cardiac and skeletal muscles. The purpose of this review is to provide a comprehensive understanding of the critical role TTN mutations play in DCM and other forms of cardiomyopathy. With the advent of next-generation sequencing (NGS), it has become feasible to simultaneously analyse numerous genes, including large and complex ones such as TTN. TTN truncations are frequently observed in dilated cardiomyopathy (DCM), whereas they are comparatively rare in hypertrophic cardiomyopathy (HCM). Furthermore, TTN mutations have been implicated in arrhythmogenic right ventricular cardiomyopathy (ARVC), a distinct clinical entity with characteristic features and outcomes. The discovery of a rare TTN missense variant that co-segregates with restrictive cardiomyopathy (RCM) strongly suggests that TTN may represent a novel causative gene in this severe cardiomyopathy. Furthermore, we highlight the significant implications of these findings for advancing both basic research and clinical practice in cardiovascular medicine.